Catalytic Version of Enediyne Cobalt‐Mediated Cycloaddition and Selective Access to Unusual Bicyclic Trienes. Issue 19 (20th March 2013) - Ventre, Sandrine; Simon, Cédric; Rekhroukh, Feriel; Malacria, Max; Amatore, Muriel; Aubert, Corinne; Petit, Marc
<x xml:space="preserve">Abstract</x> Go cyclic! The use of [Co(H)(PMe3)4] as a cobalt catalyst allows the previously unattainable catalytic version of the cobalt‐mediated cycloaddition of enediynes without the requirement of thermal or light activation (see scheme). The importance of a chelating group on the substrate that can selectively direct the reaction pathway toward the classical polycyclic 1, 3‐cyclohexadienes or a new family of bicyclic trienes is also demonstrated.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>